Novel magnesium alloy and preparation method thereof
By borizing the Mn powder and mixing it with aluminum powder, the thermal expansion behavior of the magnesium alloy is changed, and the problem of high thermal expansion coefficient of the magnesium alloy is solved, which improves its mechanical properties and plasticity in the high-temperature section, achieving low thermal expansion and excellent Combined performance of compressive strength and lightweight.
Patent Information
- Application Number
- CN202411551212.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-24
AI Technical Summary
The thermal expansion coefficient of existing magnesium alloys in the high temperature stage is relatively high, which affects its mechanical properties and reliability. To reduce the thermal expansion coefficient, a higher proportion of alloy elements or second phase is required to introduce a higher proportion, resulting in a decrease in mechanical properties.
By borizing the Mn powder and mixing it with aluminum powder and magnesium alloy powder, magnesium alloy is prepared by solid phase vacuum hot pressing sintering, changing the interface between Mn and Mg matrix, forming stress and strain mismatch, reducing magnesium Thermal expansion and the addition of Al at the same time improves the mechanical properties of the alloy.
It realizes the high-temperature stage low thermal expansion coefficient, excellent compression strength and plasticity, and has lightweight, easy operation and low price comprehensive performance.
Smart Images

Figure BDA0005115128190000051 
Figure BDA0005115128190000061 
Figure HDA0005115128200000011
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal composite materials, and in particular to a novel magnesium alloy and a preparation method thereof. Background Art
[0002] Magnesium and its alloy materials are currently the lightest metal structural materials, with a density of 1.73g / cm 3 ~1.85g / cm 3 In addition, magnesium alloys also have the advantages of high specific strength, high damping, good electromagnetic shielding, and low recycling cost, which makes magnesium alloys have great application potential in lightweight engineering in the fields of automobiles, aerospace, rail transportation, and 3C products. The thermal expansion and contraction behavior of magnesium alloy materials due to temperature changes has a great influence on the quality, service performance and reliability of components. The coefficient of thermal expansion (CTE) is usually used to describe the thermal expansion behavior of materials in the corresponding temperature range. Due to the small atomic mass of magnesium, the atomic vibration frequency is high during thermal vibration. The average CTE from room temperature to 300°C is 26×10 -6 K -1 .
[0003] At present, the CTE of magnesium alloys is often regulated by introducing alloying elements or low thermal expansion particles. However, to achieve a significant reduction in the CTE of magnesium alloys, a higher proportion of alloying elements or the introduction of a second phase is required, which will sacrifice the mechanical properties and lightweight advantages of magnesium alloys. How to reduce the thermal expansion coefficient of magnesium alloys as much as possible while maintaining the original mechanical properties of magnesium alloys and even improving the plasticity of magnesium alloys, and even reduce its thermal expansion coefficient in the high temperature range, has become an urgent problem to be solved in the field of high-temperature magnesium alloy research. Summary of the invention
[0004] The object of the present invention is to provide a new magnesium alloy and a preparation method thereof in view of the above problems.
[0005] In order to achieve its purpose, the present invention adopts the following technical solution:
[0006] A first aspect of the present invention provides a method for preparing a novel magnesium alloy, comprising the following steps:
[0007] 1) Boronizing Mn: Mn powder and B powder are mixed in a certain ratio, fully ground until the powders are evenly mixed, and then heated to stimulate the activity of Mn and B, and the Mn is subjected to boronization to obtain boronized Mn powder;
[0008] 2) mixing the boronized Mn powder obtained in step 1) with aluminum powder and magnesium alloy powder in proportion, and grinding the powders sufficiently until the powders are uniformly mixed to obtain a [Mn (boronized) + Al] / metal matrix mixed powder;
[0009] 3) The [Mn (boronized) + Al] / metal matrix mixed powder obtained in step 2) is loaded into a mold, and the [Mn (boronized) + Al] / metal matrix material is obtained by solid phase vacuum hot pressing sintering.
[0010] Preferably, in step 1), the molar ratio of Mn powder to B powder is 0.8-1.2:1; the heating is carried out by microwave-assisted heating, preferably in a microwave oven with an output power of 600-800 W for 3-10 min.
[0011] Preferably, in step 1), the microwave-assisted heating method is to put the mixed powder into a quartz tube and seal the tube under vacuum, then put the sealed quartz tube into a quartz crucible filled with graphite powder, add a layer of insulation bricks around the crucible, and heat it in a microwave oven.
[0012] Preferably, in step 1) and step 2), the grinding is performed by ball milling with a planetary ball mill;
[0013] In step 1), the ball-to-material ratio is 8 to 12:1, the rotation speed is 150 to 200 r / min, and the ball milling time is 20 to 40 min;
[0014] The ball-to-material ratio in step 2) is 8-12:1, the rotation speed is 150-200 r / min, and the ball milling time is 130-170 min.
[0015] Preferably, the magnesium alloy is WE43.
[0016] Preferably, in step 2), the mass ratio of the Mn powder after the boronization treatment to the aluminum powder and the magnesium alloy powder is 6-8:0-10:82-94.
[0017] Preferably, in step 2), the mass ratio of the Mn powder after the boronization treatment to the aluminum powder and the magnesium alloy powder is 6-8:3-10:82-91 or 6-8:5-10:82-89 or 7:3-10:83-90 or 7:5-10:83-88 or 7:7-10:83-86 or 7:8-10:83-85 or 7:8-9:84-85 or 7:9-10:83-84.
[0018] Preferably, in step 3), the sintering temperature of the solid phase vacuum hot pressing sintering is 500-550° C., the sintering pressure is 15-25 MPa, and the heat preservation and pressure holding time is 0.5-1.5 h.
[0019] Preferably, in step 3), the hot pressing sintering furnace is first evacuated to a vacuum of 1×10 -5 Pa, and heat from room temperature to 520°C at a heating rate of 15-25°C / min, while pressurizing to 20MPa, and keep warm for 1h.
[0020] The second aspect of the present invention provides a new magnesium alloy, which is obtained by mixing borided Mn powder, aluminum powder and magnesium alloy powder, grinding until the powders are evenly mixed, and then sintering by solid phase vacuum hot pressing, and is prepared by any of the preparation methods described above.
[0021] The beneficial effects of the present invention are:
[0022] During the preparation of magnesium alloy, a large internal stress is formed at the interface between Mn and Mg. The present invention firstly performs boronization treatment on Mn powder to change the magnetic properties of Mn, and changes the interface bonding between Mn and Mg matrix, thereby generating a large stress-strain mismatch, so that the stress on the magnesium matrix is compressive stress. During the heating process, the expansion of magnesium becomes difficult, which reduces the thermal expansion of Mg, and the added Al improves the mechanical properties of the alloy, so that the comprehensive performance of the composite material is excellent.
[0023] The present invention uses WE43 magnesium alloy as a metal matrix, and prepares [Mn (boronized) + Al] / WE43 alloy material by a method of composite addition of boronized Mn and Al. The composite addition of boronized Mn powder and Al not only makes the original WE43 magnesium alloy have a low thermal expansion coefficient in a high temperature zone, but also improves its strength and plasticity. The magnesium-based alloy with low thermal expansion, excellent compressive strength and plasticity has the characteristics of light weight, simple preparation method, low price, etc., and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the X-ray diffraction analysis result of the boronized Mn prepared in Example 1 of the present invention.
[0025] Figure 2 These are the X-ray diffraction analysis results of the 7wt.% Mn (boride treatment) + Xwt.% Al / WE43 alloy materials (X=3, 5, 7, 10) prepared in Example 1 of the present invention.
[0026] Figure 3 These are the SEM analysis results of the 7wt.% Mn (boride treatment) + Xwt.% Al / WE43 alloy materials (X=3, 5, 7, 10) prepared in Example 1 of the present invention.
[0027] Figure 4 This is an energy spectrum scan of the 7wt.% Mn (boride treatment) + 5wt.% Al / WE43 alloy material prepared in Example 1 of the present invention.
[0028] Figure 5 This is an energy spectrum scan of the 7wt.% Mn (boride treatment) + 10wt.% Al / WE43 alloy material prepared in Example 1 of the present invention.
[0029] Figure 6Thermal expansion diagram of 7wt.%Mn(boration treatment)+Xwt.%Al / WE43 alloy material (X=3, 5, 7, 10) prepared in Example 1 of the present invention, (a): thermal expansion curve diagram; (b) average thermal expansion coefficient bar graph of RT~400℃, 7* represents 7wt.%Mn(boration treatment) / WE43, 7*+X* represents 7wt.%Mn(boration treatment)+Xwt.%Al / WE43, (X=3, 5, 7, 10).
[0030] Figure 7 Mechanical properties diagram of 7wt.%Mn(borated)+Xwt.%Al / WE43 alloy material (X=3, 5, 7, 10) prepared in Example 1 of the present invention, (a): compression curve diagram; (b) compression performance analysis data: 7* represents 7wt.%Mn(borated) / WE43, 7*+X* represents 7wt.%Mn(borated)+Xwt.%Al / WE43, (X=3, 5, 7, 10). DETAILED DESCRIPTION
[0031] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0032] The experimental methods in the following embodiments are all conventional methods unless otherwise specified; the materials used are all conventional materials in the art and can be obtained commercially unless otherwise specified.
[0033] WE43 magnesium alloy is a Mg-Y-RE alloy with the chemical composition of Mg-4%Y-3%RE(Nd, Gd)-0.5%Zr and a purity of 99.9%.
[0034] Example 1: Preparation of magnesium-based alloy with low thermal expansion, excellent compressive strength and plasticity
[0035] 1. Boride treatment of Mn:
[0036] First, manganese (Mn) powder (purity 99.98%) and boron (B) powder (purity 99.9999%) were weighed in a 1:1 molar ratio, and the weighed powders were placed in a planetary ball mill for 30 minutes, with a ball mill speed of 180 r / min and a ball-to-material ratio of 10:1.
[0037] The evenly mixed powder was put into a quartz tube and sealed under vacuum. The sealed quartz tube was then placed into a quartz crucible filled with graphite powder. A layer of insulating bricks was added around the crucible. The mixture was heated in a microwave oven with an output power of 700 W for 8 minutes to obtain a manganese-boron mixture, which was then sampled for later use.
[0038] 2. Preparation of 7wt.%Mn(boride treatment)+Xwt.%Al / WE43 alloy material
[0039] Aluminum (Al) powder (particle size 1-3 μm), boronized Mn powder obtained in step 1, and metal matrix WE43 powder (200 mesh) were weighed and mixed evenly in a planetary ball mill to obtain a mixed powder. The amount of boronized Mn powder was 7wt%, the amount of Al powder was set to five different proportions (0, 3wt%, 5wt%, 7wt%, 10wt%), and the remainder was WE43 powder (i.e., boronized Mn wt% + Al wt% + WE43 wt% = 100%). The obtained mixed powder was recorded as 7wt.% Mn (boronized) + Xwt.% Al / WE43 mixed powder (X = 3, 5, 7, 10). The ball-to-material ratio of the ball milling mixture was 10:1, the ball milling time was 2.5h, and the ball mill speed was 180r / min.
[0040] 3. Solid phase vacuum hot pressing sintering
[0041] The ball-milled and mixed 7wt.% Mn (boronized) + Xwt.% Al / WE43 powder was placed in a graphite mold, and the preparation of 7wt.% Mn (boronized) + Xwt.% Al / WE43 alloy material was completed in a vacuum hot pressing sintering furnace: the mixed powder was placed in a hot pressing sintering furnace and vacuumed to 1×10 -5 Pa, heated from room temperature to 520°C at a rate of 20°C / min, pressurized to 20MPa, kept at this temperature for 1h, and cooled with the furnace.
[0042] Example 2: Product testing
[0043] (1) X-ray diffraction analysis
[0044] The manganese-boron mixture prepared in Example 1 was subjected to X-ray diffraction analysis, and the results were as follows: Figure 1 As shown. Figure 1 It can be seen that there is no B peak in the X-ray diffraction peak of the prepared manganese-boron mixture except the treated Mn peak, indicating that the B element exists in Mn in a certain way during the microwave-assisted heating process.
[0045] X-ray diffraction analysis was performed on the 7wt.% Mn (boride treatment) + Xwt.% Al / WE43 alloy material (x=3, 5, 7, 10) prepared in Example 1. The results are as follows: Figure 2 In 7wt.% Mn (boration treatment) + Xwt.% Al / WE43, there is an obvious Mg diffraction peak, in addition to Al2Y peaks and a small amount of Y2O3 and MgO peaks. No other phases are found, indicating that the Mn and B treated by boration have almost no reaction with the matrix.
[0046] (2) SEM / EDS microstructure and composition analysis
[0047] The prepared 7wt.%Mn(boronized)+Xwt.%Al / WE43 composite material was analyzed by SEM and EDS. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3 As shown in (a), when the Al addition amount is 3wt.%, a network is formed around the magnesium matrix in the microstructure of the alloy, resulting in loose bonding between the matrix and a decrease in its mechanical properties. However, with the increase of Al content, the network disappears and the second phase particles are segregated along the grain boundaries. The higher the Al content, the more segregation occurs, thereby increasing defects such as dislocations at the grain boundaries, bringing second phase strengthening to the sample and improving its compressive strength.
[0048] The EDS spectrum scan of 7wt.%Mn(boride treatment)+5wt.%Al / WE43 sample is as follows: Figure 4 As shown, from Figure 4 It can be seen that part of the Nd element diffuses into the Mn element, which may react with the borided Mn, changing the magnetic moment and causing changes in performance. At the same time, Al is evenly distributed in the sample, regulating the interface bonding and stress distribution between the borided Mn and the matrix, and affecting the thermal expansion coefficient of the composite material. At the same time, Al will dissolve in Mg and promote the migration of B in Mg, so that during the hot pressing cooling process, part of Al and B will dissolve in Mg, increasing the Mg lattice and retaining it at room temperature. During the thermal expansion measurement, the volume that should have expanded due to the increase in temperature has already been reached at room temperature, so the volume change is reduced and the thermal expansion coefficient is reduced.
[0049] The EDS spectrum scan of 7wt.%Mn(boride treatment)+10wt.%Al / WE43 sample is as follows: Figure 5 As shown, from Figure 5 It can be seen that the Al element is distributed around Mn, promoting the segregation of Mn, resulting in a large number of dislocations around the grain boundaries, greatly improving its mechanical properties.
[0050] (3) Thermal expansion performance analysis
[0051] The thermal expansion performance test of the prepared samples was carried out, and the test results were as follows: Figure 6 As shown in Table 1, Figure 6It can be seen from (a) that when the addition amount is 7wt.% Mn (boration treatment), a step appears in the temperature range of 280℃~320℃, and its thermal expansion coefficient increases from the original 27.6×10 -6 ·K -1 Reduced to 22.5×10 -6 ·K -1 . After adding Al element, the CTE value is lower than that of WE43, especially when the addition amount is 7wt.% Mn (boration treatment) + 5wt.% Al, the alloy has near-zero expansion in the high temperature range of 280℃~350℃. At the same time, it can be seen from the thermal expansion curve that after the addition of Al element, the curve presents three different stages. When the content is 3wt.% Al, the material does not produce lower thermal expansion behavior in the high temperature section; when the addition amount increases to 5wt.% and 7wt.%, the thermal expansion coefficient of the material in the high temperature section decreases; when the addition amount is 10wt.%, the thermal expansion coefficient of the high temperature section remains unchanged.
[0052] Table 1. Thermal expansion coefficients of 7wt.%Mn(boride treatment)+Xwt.%Al / WE43 alloy materials in different temperature ranges
[0053]
[0054]
[0055] (4) Mechanical properties analysis
[0056] The room temperature thermal expansion performance test of the prepared samples was carried out, and the test results of uniaxial compressive strength (UCS) and elongation (EL) were as follows: Figure 7 As shown in Table 2, although the 7wt.% Mn (boration treatment) / WE43 sample can reduce the thermal expansion coefficient in the high temperature section, the mechanical properties are significantly reduced. With the addition of Al element, the mechanical properties of the alloy appear in three stages, namely, the strength and plasticity of the 3wt.% Al content are lower than those of pure WE43, the strength of 5wt.% Al and 7wt.% Al remains unchanged and the plasticity decreases, and the strength and plasticity of 10wt.% Al are improved, corresponding to the three stages of thermal expansion.
[0057] From the results in Tables 1 and 2, when the Al element addition amount is 5wt.%, the thermal expansion coefficient of the composite material in the high temperature section is close to 0 and the mechanical properties decrease slightly, and the comprehensive performance is relatively excellent; when the Al element addition amount is 7 and 10wt.%, the comprehensive performance of the composite material is relatively excellent; when the Al element addition amount is 7wt.%, in the temperature range of room temperature to 320℃, the thermal expansion coefficient of the composite material is low, the strength is improved, and the strength and plasticity decrease slightly; when the Al element addition amount is 10wt.%, the strength and strength and plasticity of the composite material are improved, and the thermal expansion coefficient is also lower than that of the WE43 sample.
[0058] Table 2. Room temperature compression properties of 7wt.%Mn (boride treatment) + Xwt.%Al / WE43 alloy material
[0059] Sample UCS(MPa) EL(%) WE43 311 23.3 7wt.%Mn(boride treatment) / WE43 158 12.4 7wt.%Mn(boride treatment)+3wt.%Al / WE43 164 12.5 7wt.%Mn(boride treatment)+5wt.%Al / WE43 297 18.7 7wt.%Mn(boride treatment)+7wt.%Al / WE43 319 19.1 7wt.%Mn(boride treatment)+10wt.%Al / WE43 503 24.4
Claims
1. A method for preparing a novel magnesium alloy, characterized in that: The steps include: 1) Boronizing Mn: Mn powder and B powder are mixed in a certain ratio, fully ground until the powders are evenly mixed, and then heated to stimulate the activity of Mn and B, and the Mn is subjected to boronization to obtain boronized Mn powder; 2) mixing the boronized Mn powder obtained in step 1) with aluminum powder and magnesium alloy powder in proportion, and grinding the powders sufficiently until the powders are uniformly mixed to obtain a [Mn (boronized) + Al] / metal matrix mixed powder; 3) The [Mn (boronized) + Al] / metal matrix mixed powder obtained in step 2) is loaded into a mold, and the [Mn (boronized) + Al] / metal matrix material is obtained by solid phase vacuum hot pressing sintering.
2. The preparation method according to claim 1, characterized in that: In step 1), the molar ratio of Mn powder to B powder is 0.8-1.2:1; the heating is carried out by microwave-assisted heating, preferably in a microwave oven with an output power of 600-800W for 3-10 minutes.
3. The preparation method according to claim 2, characterized in that: In step 1), the microwave-assisted heating method is to put the mixed powder into a quartz tube and seal the tube in vacuum, then put the sealed quartz tube into a quartz crucible filled with graphite powder, add a layer of insulation bricks around the crucible, and heat it in a microwave oven.
4. The preparation method according to claim 1, characterized in that: In step 1) and step 2), the grinding is performed by ball milling with a planetary ball mill; In step 1), the ball-to-material ratio is 8 to 12:1, the rotation speed is 150 to 200 r / min, and the ball milling time is 20 to 40 min; The ball-to-material ratio in step 2) is 8-12:1, the rotation speed is 150-200 r / min, and the ball milling time is 130-170 min.
5. The preparation method according to claim 1, characterized in that: The magnesium alloy is WE43.
6. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the Mn powder after the boronization treatment to the aluminum powder and the magnesium alloy powder is 6-8:0-10:82-94.
7. The preparation method according to claim 1, characterized in that: In step 2), the mass ratio of the Mn powder after the boronization treatment to the aluminum powder and the magnesium alloy powder is 6-8:3-10:82-91 or 6-8:5-10:82-89 or 7:3-10:83-90 or 7:5-10:83-88 or 7:7-10:83-86 or 7:8-10:83-85 or 7:8-9:84-85 or 7:9-10:83-84.
8. The preparation method according to claim 1, characterized in that: In step 3), the sintering temperature of the solid phase vacuum hot pressing sintering is 500-550° C., the sintering pressure is 15-25 MPa, and the heat preservation and pressure holding time is 0.5-1.5 h.
9. The preparation method according to claim 8, characterized in that: In step 3), the hot pressing sintering furnace is first vacuumized to 1×10 -5 Pa, and heat from room temperature to 520°C at a heating rate of 15-25°C / min, while pressurizing to 20MPa, and keep warm for 1h.
10. A novel magnesium alloy, characterized in that: The boronized Mn powder, aluminum powder and magnesium alloy powder are mixed, ground until the powders are evenly mixed, and then sintered by solid phase vacuum hot pressing. The preparation method according to any one of claims 1 to 9 is used to prepare the powder.
